Photon Echoes Made Simple. Issue 2 (1983) - Beach, R.; Brody, B.; Hartmann, S. R.
Abstract : Photon Echoes in gases are analyzed via the Billiard Ball Echo Model both in the short and long pulse limit where the "atoms" are represented as spherical and elliptical billiard balls, respectively. Recent experiments demonstrating the elliptical billiard ball shape are presented using intensity data which ranges over close to eleven orders of magnitude.